Hybrid Trust-Based Models and Protocols for Enhanced Security and Performance in Dynamic Wireless Sensor Networks and Wireless Ad Hoc Networks - Seshagiri Rao Ganta; Naga Malleswara Rao Nallamothu (ITEGAM-JETIA)
Wireless Sensor Networks (WSNs) and Wireless Ad Hoc Networks (WANETs) are crucial for real-time applications, yet they encounter several obstacles, including the preservation of data privacy, ensuring node integrity, and optimizing path planning—especially when implemented in dynamic, large-scale environments. Conventional methods frequently lack cohesive systems for trust management and node verification, which results in security vulnerabilities and performance shortcomings. This study introduces innovative hybrid trust-based models and protocols aimed at overcoming these challenges. For dynamic WSNs, a hybrid approach utilizing Ant Colony Optimization (ACO) is proposed that seamlessly integrates node trust probability with path planning and is further enhanced by both local and global update strategies. In the context of WANETs, we unveil a non-linear integrity-based intrusion detection model, complemented by a hybrid security protocol that combines an integrity-centric approach with an encryption framework for secure node-to-node communication. The experimental outcomes of these studies highlight substantial advancements compared to traditional techniques, demonstrating improvements in numerous aspects such as runtime efficiency, hash variations, privacy protection, route overhead, packet delivery rates, delays, throughput, and overall security. These strategies exemplify the effectiveness of hybrid trust-based and integrity-oriented solutions in strengthening both security and performance within contemporary wireless networks.